Effects of manual therapy in people with fibromyalgia: Systematic review and meta-analysis - Concha Valdevenito, Denisse Elizabeth.; Chacón Pérez, Danithza B.; Cereceda Muriel, Christopher Felipe.; Valdés Silva, Marianna. (Fundación Universitaria María Cano, 2024)
Objective. The aim of this systematic review with meta-analysis is to synthesize the available scientific evidence on the effects of manual therapy applied in isolation in comparison to other interventions on pain, functional capacity, global impression of improvement, and self-perceived severity of symptoms in people with fibromyalgia. Methodology. A systematic review with meta-analysis was conducted with electronic search of MEDLINE, WoS, SCOPUS, PEDro, CENTRAL, and LILACS. Results. Eleven studies met the selection criteria and six were included in a quantitative synthesis. Pain at the end of treatment had a mean difference of-0.42 (95% CI-1.14, 0.30, p = 0.25), functional status at the end of treatment had a mean difference of-0.15 (95% CI-0.69, 0.40, p = 0.60), the global impression of health at the end of treatment had a mean difference of-1.13 (95% CI-1.68,-0.57 p = <0.00) and a mean difference of-0.48 after twelve months (95% CI-0.78,-0.19 p = <0.00), the global impression of severity after the intervention had a mean difference of-0.62 (95% CI-1.22,-0.03, p = 0.04) and a mean difference of-0.43 after twelve months (95% CI-1.18, 0.32, p = 0.26). Conclusions. Isolated manual therapy is an intervention that could significantly improve the self-perception of the global state of improvement and severity of symptoms in the short term compared to sham physical agents. However, it is not better than other interventions to reduce pain and improve functional capacity.
Efectos de la terapia manual en personas con fibromialgia: Revisión sistemática y metaanálisis
Keywords: Manual therapy; Systematic review; Dolor crónico; Fibromialgia; Meta-análisis; Sistema musculoesquelético